Speech Intervention for Deaf-Autistic Students in Addressing Difficulties in Arabic Letter Pronunciation - Rika Astari; Yusroh; Djamaluddin Perawironegoro; Tri Purwanti; Muhammad Irfan Faturrahman; Supardi (LISANIA: Journal of Arabic Education and Literature, 2026)
Speech intervention for deaf-autistic students is a crucial yet under-researched area within Qur'an learning framework. Previous scholarship predominantly features visual and sign-language media, frequently neglecting touch-based articulation therapies like anatomical massage. This study aims to delineate targeted speech intervention models for deaf- autistic students and analyze the clinical factors dictating their implementation. Utilizing a qualitative descriptive design, primary data were gathered through field investigations at Qotrunnada Islamic Special School (SLB) in Bantul, Yogyakarta. The research subjects comprised four deaf- autistic students differentiated by age, hearing-loss severity, and behavioral spectrums. Data validation was secured via collaborative data triangulation involving the clinical expert consultant. The findings establish three primary empirical components of the intervention: (1) structured facial and lip desensitization massage, (2) targeted tongue placement training using customized spatels, and (3) systematic phonetic articulation drillings. Based on these components, the study presents three distinct pedagogical typologies categorized according to the students’ neurological and auditory baseline capacities. These results demonstrate that speech proficiency outcomes are strictly conditional upon individual attention spans and speech-organ elasticity rather than visual stimuli alone. Ultimately, this systemic framework provides an evidence-based roadmap for special education practitioners developing tactile speech therapy instruments for multi-disabled learners.